Pertumbuhan Gracilaria sp. yang Dibudidayakan Pada Tambak di Bajo Baru Dompu - Ulfa Yulistiana; Ayu Adhita Damayanti; Nunik Cokrowati (Rekayasa, 2020)
Gracilaria sp. is a seaweed that produces "agar" and has economic value. Market demand for Gracilaria sp. is quite high but has not yet been fulfilled. Gracilaria sp. has not been widely cultivated in the waters of West Nusa Tenggara Province, including Dompu. If the level of production of Gracilaria sp. high, it can improve the community's economy. So it is necessary to increase cultivation to increase the production of Gracilaria sp. This research aims to study the growth of Gracilaria sp. cultivated with different initial seed weight treatment. The research was conducted in the Bajo Baru pond, Dompu, West Nusa Tenggara. This study used a completely randomized design method consisting of five treatments with three repetitions. The treatments were: treatment A; Gracilaria sp. with initial seed weight of 100 gr (control); treatment B: Gracilaria sp. with an initial seed weight of 375 g; treatment C: Gracilaria sp. with an initial seed weight of 425 g; treatment D: Gracilaria sp. with initial seed weight 475 g; treatment E: Gracilaria sp. with initial seed weight of 575 g. The parameters observed were absolute and daily growth, agar yield, and water quality. Cultivation and parameter observation was carried out for 30 days. Data analysis using ANOVA (Analysis of Variance) and graphs with descriptive analysis. The results showed that the initial seed weight of Gracillaria sp had no significant effect on absolute and daily growth. The best growth was obtained in treatment E (575 g) which gave 740 g absolute growth and 0.052 g daily growth. On the other hand, the yield value for agar shows a decreasing trend when using seeds with a higher initial weight. The yield value for the highest order was 17.56%.